Short Communication: The effect of ethylene glycol as plasticizer against mechanical properties of bioplastic originated from jackfruit seed starch and cocoa pod husk - MAULIDA LUBIS; MARA BANGUN HARAHAP; M. HENDRA S. GINTING; SITI MAYSARAH; ARIF GANA (Smujo International, 2018)
Lubis M, Harahap MB, Ginting MHS, Maysarah S, Gana A. 2018. Short Communication: The effect of ethylene glycol as plasticizer against mechanical properties of bioplastic originated from jackfruit seed starch and cocoa pod husk. Nusantara Bioscience 10: 76-80. The addition of elasticity of bioplastic from jackfruit seed starch reinforced with cacao pod husk was studied using ethylene glycol as plasticizer. This study aimed to investigate the effect of addition of ethylene glycol as plasticizer against mechanical properties of bioplastic from jackfruit seed starch and cacao pod husk. Bioplastic was made by casting method at temperature 88.1 ?C with ratios of cacao pod husk as fillers and jackfruit seed as starch were 9:1, 8:2, 7:3, 6:4, and 5:5 (w/v). The variations of ethylene glycol were from 0.2 (v/w) to 0.4 (v/w). The result showed that ethylene glycol could increase the mechanical properties of bioplastic. The best condition of bioplastic was achieved at ratio 7:3 in addition of ethylene glycol was 0.2 (v/w) with tensile strength of 15.40 MPa and elongation at break 2.39%. The result of FT-IR analysis indicated that bioplastics consisted of O-H group, C-H group, C=O group and C-O group. The SEM images demonstrated the bioplastic with cacao pod husk as filler and ethylene glycol as plasticizer had the fracture surfaces with the compact structure compared to that bioplastic without fillers.